As Implicações biopolíticas da pandemia do coronavírus no Brasil - ALBUQUERQUE, Thalia Bandeira Ferreira (2022)
The debate on the socio-political repercussions of the pandemic in Brazilian society is necessary and relevant, in the face of the inaction of the current president Jair Messias Bolsonaro throughout the pandemic period and in the face of his total disdain for the large number of deaths from the disease in the country. Thus, it becomes necessary to build and develop research that understands and explains to the community how this health crisis of 2020 directly influences Brazilian politics, the economy and society in the most negative way possible. In this sense, in this work, the reflections of several classic and modern authors will be analyzed and interpreted to understand the posture of the Brazilian State in combating the Covid-19 pandemic. To this end, the methodology used consisted of bibliographic research, whose theoretical references were reviews of books and articles by various authors that deal, in general, with the concepts of biopolitics and pandemic, based on philosophers such as Giorgio Agamben approaching critically about biopolitical devices and metropolis, Michel Foucault teaching about biopower and the use of epidemics as a form of social control and Achile Mbembe, who deals with necropolitics and the issue of anti-black racism in the face of the virus crisis.